THE CORRELATION BETWEEN STUDENTS’ VOCABULARY MASTERY AND THEIR READING COMPREHENSION AT THE SEVENTH GRADE STUDENTS’ OF MTs DAARUL IHSAN - Bahri, Dasep Samsul (IKIP Siliwangi, 2018)
The study investigated the correlation between students’ vocabulary mastery and their reading comprehension. Data were collected from 32 seventh grade students. The test item of vocabulary mastery and reading comprehension were given to the students to measure their level of vocabulary mastery and reading comprehension. The results were compared to find out the correlation between those variables. Showed that there was the strong correlation between students’ vocabulary mastery and their reading comprehension. The current study concluded that students’ experiences’ experiences and reading strategies help the students to understand text but vocabulary was more contributive in helping the students to comprehend the texts.